2019
DOI: 10.1021/acsami.9b10620
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Plasma Meets Cell: Plasma Tailoring by Living Cells

Abstract: The applications of the cold atmospheric plasma jet (CAPJ) in cancer treatment have been investigated for over a decade, focused on the effect that the CAPJ creates on cancer cells. Here we report for the first time on the impact that cells have on the CAPJ during treatment. To better understand these CAPJ–cell interactions, we analyzed the CAPJ behaviors in the presence of several normal and cancer cell lines and investigated the CAPJ selectivity. A more in-depth study of plasma self-organization patterns uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 42 publications
3
32
0
Order By: Relevance
“…This journal is © The Royal Society of Chemistry 2020 source when the CAP jet contacts different cell lines. 130 It is promising that we may see that many new unknows about the biological impact of bulk CAP, such as potential physical effect. 131,132…”
Section: Review Materials Advancesmentioning
confidence: 99%
“…This journal is © The Royal Society of Chemistry 2020 source when the CAP jet contacts different cell lines. 130 It is promising that we may see that many new unknows about the biological impact of bulk CAP, such as potential physical effect. 131,132…”
Section: Review Materials Advancesmentioning
confidence: 99%
“…CAP jets have, for instance, been recently demonstrated to be self‐adaptive toward cancer cells and can be fine‐tuned to maximize selectivity during plasma treatment. [ 201 ] Plasma‐activated medium (PAM) is another interesting new proposition, wherein a CAP‐activated medium, comprising of RNS and ROS, acts as a therapeutic agent with antitumor effects. [ 202 ] A recent study by Bhatt et al [ 203 ] have also shown that novel plasma‐activated solutions (PAS) can be used for antimicrobial efficacy against bloodstream catheter‐associated multidrug‐resistant infections and recurrent episodes of pathogenesis.…”
Section: Future Prospects Of Plasma Processing In Healthcare: the Road Aheadmentioning
confidence: 99%
“…Normal astrocytes hTERT/E6/E7 and glioblastoma cells U87MG have grown on the negative-x (left) region and the positive-x (right) region, respectively. Permission from Lin et al [138] the CAP-treated medium without and with cells. [140] When the volume of medium was adequately small, cellbased H 2 O 2 generation could reach about 60 μM (Figure 11a).…”
Section: Specific Cell-based H 2 O 2 Generationmentioning
confidence: 99%